Pengaruh Kompensasi, Lingkungan Kerja dan Stres Kerja terhadap Produktivitas Kerja pada Komunitas Gojek Ojol Boulbin di Wilayah Boulevard Bintaro - Novi Nuristbeathi; Nuraeni Nuraeni (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2026)
Work productivity is a critical factor in sustaining performance within gig economy communities, particularly among online motorcycle taxi drivers whose work patterns differ from those in formal organizations. Previous studies report inconsistent findings regarding the influence of compensation, work environment, and work stress on productivity, indicating the need for further investigation in non-traditional work settings. This study aims to examine the effects of compensation, work environment, and work stress on work productivity among members of the Gojek Ojol Boulbin Community in the Boulevard Bintaro area. A quantitative associative approach was employed, using saturated sampling with 60 driver respondents. Data were collected through structured questionnaires and analyzed using multiple linear regression with SPSS software. The results reveal that compensation and work environment have negative but insignificant effects on work productivity, indicating that these factors are not primary determinants in this gig-based work context. In contrast, work stress shows a positive and significant effect on productivity, suggesting that moderate levels of stress can function as a motivating factor that encourages drivers to optimize their working time and performance. These findings highlight the importance of psychological factors over structural factors in influencing productivity within platform-based work environments.